E-Cigarette Markets and Policy Responses in Southeast Asia: A Scoping Review - Yvette van der Eijk; Grace Tan; Suan Ong; Grace Tan; David Li; Dijin Zhang; Loo Shuen; Kee Seng Chia (Kerman University of Medical Sciences, 2022)
Background The global e-cigarette market has proliferated and is increasingly dominated by transnational tobacco companies. While Southeast Asian countries have received relatively little attention in e-cigarette research, the region represents an area of potentially untapped growth for the industry. We review the e-cigarette situation in Southeast Asia in terms of the e-cigarette markets, advertising and promotion of e-cigarettes, reported health impacts of e-cigarette use, and policy responses in the region. Methods  We examined e-cigarette market data from the Euromonitor Global Market Information Database (GMID) Passport database, searched in the academic literature, grey literature and news archives for any reports or studies of e-cigarette related diseases or injuries, e-cigarette marketing, and e-cigarette policy responses in Southeast Asian countries, and browsed the websites of online e-cigarette retailers catering to the region's active e-cigarette markets.  Results In 2019, e-cigarettes were sold in six Southeast Asian markets with a total market value of $595 million, projected to grow to $766 million by 2023. E-commerce is a significant and growing sales channel in the region, with most of the popular or featured brands in online shops originating from China. Southeast Asian youth are targeted with a wide variety of flavours, trendy designs and point of sale promotions, and several e-cigarette related injuries and diseases have been reported in the region. Policy responses vary considerably between countries, ranging from strict bans to no or partial regulations. Conclusion Although Southeast Asia's e-cigarette market is relatively nascent, this is likely to change if transnationals invest more heavily in the region. Populous countries with weak e-cigarette regulations, notably Indonesia, Malaysia, Vietnam and the Philippines, are desirable targets for the transnationals. Regulatory action is needed to prevent e-cigarette use from becoming entrenched into these societies, especially among young people.